Uso dos serviços de saúde bucal no Brasil: resultados da pesquisa nacional de saúde, 2019 - CORRÊA, Anderson Roberto de Sales (2023)
This study aimed to identify access to oral health services in Brazil. A descriptive cross-sectional study was carried out from the PNS 2019 database, using the STATA 14 software, relating the conditions of access to the oral health service with independent variables through Pearson's chisquare test, association by logistic regression in the bivariate and multivariate model. Based on the calculations performed, an estimate of 83,624,648 users with access to the dentist in 12 months was obtained. The young population had greater access with 54.95% (CI95%: 53.18- 56.72). Users with 11 or more years of study showed a frequency of 69.74% (CI95%: 68.56- 70.88), with a positive association as the level of education increases. Most consultations were held in the private sphere (73.92%/CI95%: 72.42-75.36). The South region had the best 12 prevalence of access in the country. It is concluded that, despite advances in oral health policies in the SUS, expansion and implementation of the ESB, it is still insufficient for the population's demand.